Pengaruh Pendidikan Kewirausahaan, Lingkungan Keluarga, dan Penggunaan Media Sosial Terhadap Minat Berwirausaha - Putri, Riselsa Salsabila; Muis, Indra (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Unemployment in Indonesia remains an important issue, particularly among vocational high school (SMK) graduates, who recorded the highest Open Unemployment Rate at 8.63%. This study aims to analyze the influence of entrepreneurship education, family environment, and social media usage on the entrepreneurial interest of 11th and 12th grade students at SMKN 8 Bekasi City. This research employed a quantitative method using a simple random sampling technique involving 257 respondents. The data were analyzed using classical assumption tests, multiple linear regression analysis, and hypothesis testing with SPSS 27. The results showed that entrepreneurship education, family environment, and social media usage had a positive and significant effect on entrepreneurial interest, both partially and simultaneously (p < 0.05). Entrepreneurship education was identified as the most dominant variable with a coefficient value of (0.338). In addition, these three variables were able to explain 46.3% of the variance in entrepreneurial interest (R² = 0.463). These findings indicate that improving entrepreneurship education, strengthening family support, and utilizing social media positively can enhance the entrepreneurial interest of vocational high school students.